x2 - 2x = ( - 2)(3 - x)
LHS = x2 – 2x
RHS = ( - 2)(3 - x) = - 6 + 2x
∴ x2 - 2x = - 6 + 2x
Or x2 - 2x + 6 – 2x = 0
⇒ x2 + 6 which is of the form ax2 + bx + c = 0
∴ it is a quadratic equation.
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Introduction to Linear Equations in Two Variables62 mins
Pair of Linear Equations-Yahaan se laye marks57 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :